Productivity of triploid aspen crops in various forest growing conditions of the Leningrad region - Boitsov Aleksandr; Zhigunov Anatoly; Zimireva Violetta (BIO Web of Conferences)
The use of various methods of mechanical tillage, which correspond to the forest growing conditions of the forest-cultivated area, makes it possible to obtain high productivity indicators of triploid aspen crops. In rich, well-drained conditions, where there is no need for surface amelioration, planting on no-tillage soil or in micro-raisings is possible. In the presence of permanent or temporary excessive humidity, it is necessary to apply plow tillage with different depths of the drainage ditch. In almost all sample plots triploid aspen at the age of 9-11 years showed better parameters compared to aspen taken as a control.